Unlocking the potential of management control systems: the role of board effectiveness, strategic decision-making, and organizational context - Adwimurti, Yudhistira; Lumbantobing, Sabar Pardamean; Rahmani, Hani Fitria; Tampubolon, Ricky Bryan (Enrichment : Journal of Management, 2024)
This research aims to analyze the influence of board effectiveness and strategic decision-making on the effectiveness of management control systems (MCS) with organizational context as a moderating variable in cyclical and non-cyclical sector companies in Indonesia. Using a quantitative approach with a cross-sectional design, data was collected through questionnaires from 127 members of the board of directors and top management of companies listed on the Indonesia Stock Exchange in 2023. Hierarchical regression analysis was used to test the research hypothesis. The research results show that board effectiveness and strategic decision-making have a significant positive effect on MCS effectiveness. Organizational context is proven to moderate the relationship between these two independent variables and MCS effectiveness, where the influence is stronger in a more dynamic and complex organizational context. The research model was able to explain 61.5% of the variation in MCS effectiveness. This research provides a theoretical contribution to the development of MCS literature by integrating the perspectives of corporate governance, strategic decision making, and contingency theory. Practically, the research results provide insight for public companies in Indonesia in designing and implementing effective MCS by considering the role of the board of directors, the quality of strategic decision making, and the organizational context